Rice is one of the most important crops for human beings, thus increasing productivity are continually persecuted. Blast disease can reduce the rate of productivity of rice cultivation. Therefore, the program of blast disease-resistant varieties needs to do effectively. One of broad-spectrum blast disease-resistant gene is Pi33. This study was aimed to identify the variation in the sequence of nucleotide bases of Pi33 gene in five interspesific lines which derived from Bio46 (IR64/Oryza rufipogo - DWINITA WIKAN UTAMI; KALIA BARNITA; SITI YURIAH; IDA HANARIDA (HAYATI Journal of Biosciences, 2011)
Rice is one of the most important crops for human beings, thus increasing productivity are continually persecuted. Blast disease can reduce the rate of productivity of rice cultivation. Therefore, the program of blast disease-resistant varieties needs to do effectively. One of broad-spectrum blast disease-resistant gene is Pi33. This study was aimed to identify the variation in the sequence of nucleotide bases of Pi33 gene in five interspesific lines which derived from Bio46 (IR64/Oryza rufipogon) and CT13432 crossing. DNA of five rice lines were amplified using the spesific primer for Pi33, G1010. Amplification results purified through Exonuclease 1 and Shrimp Alkaline Phosphatase protocols. Labelling using fluorescent dyes done before sequencing nucleotide base using CEQ8000 instrument. The results showed that lines number 28 showed introgesion of the three control parent genome (subspecies of Indica, subspecies of Japonica, and O. rufipogon) while the Lines number 79, 136, and 143 were identical to Indica genome. Strain number 195 was identical to Japonica genome. These broad genetic background lines promise as durable performance to attack the expansion of the dynamic nature of the pathogen to blast. The result of ortholog sequence analysis found conserved nucleotide base sequence (CAGCAGCC) which involved in heterotrimeric G-protein group. This protein has role as plant receptor for recognizing pathogen elicitor in interaction of  rice and blast pathogen.